Adverse Reactions in Whole Blood Donors - Venkatesh, Veenaa; T.M, Karthikeyan (International Journal of Pathology, 2018)
Background: Human blood is the most precious and essential element of human life. Safe and adequate blood supply is a big challenge in developing countries like India. Voluntary blood donors tolerate blood donation very well.Objective: The aim of the study is to estimate and possibly avoid the cause of donor adverse reactions.Materials & Methods: The study was conducted over a period of one year from January 2017 to December 2017. The donor population consisted of 2455 donors of which 1823 were males and 632 were females. Donor adverse reactions were analyzed.Results: Only 16 (0.007%) donors had adverse reactions like sweating, giddiness, pain, itching and pallor. None suffered severe adverse reactions in the study.Conclusion: Although number of donors who had adverse reactions were low, it is desirable to further reduce the rate of adverse reactions so that repeat blood donations by the population can be promoted